PEMETAAN DAN ANALISA KAWASAN PERMUKIMAN KUMUH DI OBJEK WISATA PANTAI PADANG - Suci Allara Putri; Helfia Edial (JURNAL BUANA, 2021)
This study aims to determine : 1)The information of slum area and the causes of slum settlements in Padang beach tourism objects. 2)Damage to the attraction of tourist objects due to the emergence of slum settlements to visitors at Padang beach attraction. This type of research is classified as a mixed method with a qualirative approach and a quantitative approach that aims to collect information and combine two pieces of information with different or combined approach. The results of this study were the formation of slum settlements with slum indicators divided into therr, namely light slum areas (25,259 Ha), moderate slum areas (42,374 Ha) and heavy slum areas (23,285 Ha). As well as the attractiveness of tourist objects of slum settlements with the opinions of visitor who have different views, but visitors think that Padang beach is still in the cool and beautiful category even thought it still has deficienvies in various aspects and the emergence of slum settlements has an influence on Padang beach tourism object such as conditions disturbed environment of tourist abjects, reduced natural beauty and visitor comfort, emvironmental pollution, air to local revenue and decreased income of traders around tourist objects.